Fixed income markets in Asia - Ang, Alvin Wei Wen (2009)
This research project focuses on the fixed income markets in Asia. It aims to educate financial institutions and academia on the development of the fixed income market in Asia and provide valuable insights on the development and growth trends of such markets going forward in today’s dynamic economy.